Strategic Analysis of International Oil and Gas Companies’ Response to Global Carbon Emission Reduction Initiatives - Budi Prasetyo; Utomo Sarjono Putro (Applied Quantitative Analysis, 2024)
This study investigates the role of oil and gas companies, particularly INDOPERTA, in mitigating global carbon emissions among rising energy demands and a shift toward coal and oil. This study highlights the urgency for strategic energy realignment and cleaner, sustainable sources, drawing from International Energy Agency (IEA) reports and various studies. The objective is to understand how companies such as INDOPERTA can integrate operations with effective carbon emission reduction strategies. A mixed-methods approach is employed, combining qualitative analysis of stakeholder perspectives with the AHP to prioritize initiatives based on identified criteria. Findings reveal compliance and regulation and leadership as critical areas needing focused resource allocation. The AHP analysis underscores the strategic importance of renewable energy investment and the pivotal role of leadership and innovation. It suggests a multifaceted approach involving regulatory adherence, international cooperation, and leadership development for effective carbon reduction. The study concludes that international oil and gas companies are at a crucial juncture. They must align their operations with global environmental goals and innovate to remain relevant in the climate agenda. It provides a roadmap for strategy realignment toward sustainability. However, this study has limitations, including its geographical focus, the dynamic nature of the industry, subjectivity in qualitative research and AHP, and reliance on secondary data. These findings highlight the need for ongoing research that adapts to industry changes and global carbon reduction efforts, ensuring that strategies remain relevant and effective.